The EU Green Industrial Policy for Hydrogen Economy Development - Brusiło, Paweł (Zielona polityka przemysłowa Unii Europejskiej na rzecz rozwoju gospodarki wodorowej, 2023)
This article examines the significance of green industrial policy in advancing the hydrogen economy within the European Union, and explores how hydrogen, as a versatile energy carrier, offers a solution for decarbonising sectors where emission reduction is both urgent and challenging. The evolution of the hydrogen economy, from its initial concept linked to nuclear power to its current association with renewable energy sources, is outlined, emphasising its potential to reduce carbon emissions and its growing significance in the EU’s energy mix. First, the author discusses the strategic planning in economic policy and then delves into the concept of green industrial policy, its theoretical underpinnings, and empirical evidence from the EU. The focus then shifts to the EU’s hydrogen strategy, including its objectives and critical actions for developing the hydrogen economy. The article discusses the role of hydrogen in the EU’s green industrial policy, specifically in energy, transportation, and heavy industry sectors, and the efforts to increase the use of renewable hydrogen. The conclusion highlights the multifaceted functions of green industrial policy in addressing market failures, fostering new pathways, and disrupting the old ones, and how the EU’s approach to developing a hydrogen economy exemplifies this policy. The research, confined to 2019-2023, provides insights into integrating environmental considerations in industrial policy, suggesting that the EU’s strategy and policy serve as a model approach in this domain.
Ekonomia XXI Wieku = Economics of the 21st Century, 2023, Nr 26, s. 17-26
Keywords: hydrogen economy; green industrial policy; European Union; gospodarka wodorowa; zielona polityka przemysłowa; Unia Europejska